On the union of graded prime ideals - TEKİR, ÜNSAL (DE GRUYTER OPEN LTD, 2016)
In this paper we investigate graded compactly packed rings, which is defined as; if any graded ideal I of R is contained in the union of a family of graded prime ideals of R, then I is actually contained in one of the graded prime ideals of the family. We give some characterizations of graded compactly packed rings. Further, we examine this property on h - Spec(R). We also define a generalization of graded compactly packed rings, the graded coprimely packed rings. We show that R is a graded compactly packed ring if and only if R is a graded coprimely packed ring whenever R be a graded integral domain and h - dim R = 1.
Keywords: graded ring; graded prime ideal; COPRIMELY PACKED RINGS